The Impact of Ethical Orientation and Personality on Virtual Collaboration Usage - Kirby, Eric G.; Kirby, Susan L.; Konopaske, Robert; Giacalone, Robert A. (Journal of Applied Business and Economics, 2024)
This paper predicts the use of virtual collaboration using instant messaging applications in a university setting. It examines the impact of age, sex, ethical orientations, and bright and dark personality traits on the usage of virtual collaboration applications. A significant finding is younger students and women are more likely to use this type of application. While ethical relativity and egoism also predict usage, being oriented toward justice negatively relates to application utilization. In terms of personality, the bright measure of extroversion is highly significant as is the dark variable narcissism. Finally, there is a very strong negative relationship with psychopathy.